An improvement in strong designated verifier signatures. (1st January 2014) - Yang, Fuw-Yi; Liang, Ling-Ren; Hsu, Chun-Chin
Designated verifier signature schemes are applied in situations such as electronic voting and electronic auctions. Signature recipients can ascertain the contents of the document, but cannot verify the identity of the signer to a third party. This study reviewed the protocols of past researches and analysed whether these protocols would disclose signer identities under various types of attacks. The paper also proposes a strong designated verifier signature scheme that possesses more efficient calculation as well as simpler string encoding for signers. Based on the difficulty of Gap Diffie-Hellman problem and in the Standard Model, the scheme is existentially unforgeable under the adaptively chosen message attacks.